Methods for Solving Complex Problems in Fluids Engineering - Kang, Can; Liu, Haixia; Zhang, Yongchao; Mao, Ning (Springer Nature Singapore : Imprint: Springer, 2019)
This book describes recently developed research methods used to study complex problems in fluid engineering, especially optical flow measurement, flow visualization and numerical methods. It includes a wealth of diagrams and images, and the content is presented in a step-by-step manner from beginning to end, helping readers grasp the central points of the book. The book also presents a number of practical cases, illustrating how the research methods covered can be concretely implemented. Lastly, the book offers a valuable point of departure for pursuing further research.